2011
DOI: 10.1111/j.1748-5827.2011.01040.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a bipolar vessel‐sealing device in resection of canine insulinoma

Abstract: BVSD is a safe and viable alternative to conventional methods of pancreatectomy for canine insulinoma. It provides the possibility to remove insulinomas in the pancreatic limbs and corpus with relative ease. BVSD pancreatectomy in dogs with insulinoma significantly decreases operative and hospitalisation times and is not associated with more clinical complications than SF pancreatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 31 publications
(39 reference statements)
1
27
1
Order By: Relevance
“…It has been shown that the burden of contamination and wear resulting from repeated use has minimal effect on the seal quality delivered by reusable VSD . Despite this, the single‐use LigaSure is the most commonly used VSD in veterinary surgery . In particular, the 5‐mm Maryland jaw device was developed for a variety of laparoscopic surgeries .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the burden of contamination and wear resulting from repeated use has minimal effect on the seal quality delivered by reusable VSD . Despite this, the single‐use LigaSure is the most commonly used VSD in veterinary surgery . In particular, the 5‐mm Maryland jaw device was developed for a variety of laparoscopic surgeries .…”
Section: Introductionmentioning
confidence: 99%
“…6 Despite this, the single-use LigaSure is the most commonly used VSD in veterinary surgery. [8][9][10][11][12][13][14] In particular, the 5-mm Maryland jaw device was developed for a variety of laparoscopic surgeries. 1 When the jaws of this handset are closed, the handle depresses a button triggering energy application.…”
Section: Introductionmentioning
confidence: 99%
“…One such EBVS is the LigaSure (Covidien Medtronic, Minneapolis, Minnesota). This instrument is in widespread use in veterinary surgery . The manufacturer recommends the handsets be used only in a single operative procedure before being discarded .…”
Section: Introductionmentioning
confidence: 99%
“…47 Studies to examine the effectiveness and speed of these devices in procedures, collateral damage to tissue, blood loss, and use in minimally invasive surgery have been done and support their use in veterinary surgery. 22,40,45,46,[48][49][50][51][52] Benefits that have been noted include efficient and complete hemostasis of vessels, adequate arterial bursting pressure, absence of foreign material, and no need for additional ligation support. 44 In a study by Rivier and Monnet,44 it was determined that use of a vessel sealant device (Ligasure) provided adequate hemostasis and would provide adequate resistance to blood pressure in splenectomies when the splenic vessel and other associated vessels were isolated and coagulated.…”
Section: Vessel Sealing Devicesmentioning
confidence: 95%
“…Similar results supporting the efficacy of vessels sealing devices have been seen with partial liver lobectomies, partial lung lobectomies, uterine horns and bodies, ovarian pedicles and pancreas. 22,45,50,[52][53][54] SUMMARY When understood and used properly, stapling and vessel sealing devices can increase confidence of the surgeon, precision, decrease surgical time, and contribute positively to the outcome of the surgery, especially in the critically ill patient. The use of surgical stapling and vessel sealing devices should not replace good surgical and soft tissue handling techniques.…”
Section: Vessel Sealing Devicesmentioning
confidence: 99%